Copper-Mediated C–O/C–N Bond Formation: A Facile Synthesis of 3-Amidocoumarin, 3-Amidoazacoumarin, and N-Aroylindole Derivatives - Worayuthakarn, Rattana; Suddee, Nattanit; Nealmongkol, Prattya; Ruchirawat, Somsak; Thasana, Nopporn (Synlett, 2022)
Three different heterocyclic systems (3-amidocoumarins, 3-amidoazacoumarins, and N-benzoylindol-2-carboxamides) were synthesized based on the strikingly different selectivity of copper-mediated C–O/C–N bond formation from azlactones under various heating conditions. The stereochemistry of the double bond dictated the nature of the products. Microwave irradiation played an important role in the isomerization of the trisubstituted olefin leading to the formation of 3-amidocoumarins and 3-amidoazacoumarins. Three products showed promising-to-good cytotoxic activities against a panel of cancer cell lines, including HepG2 (hepatoblastoma) and MOLT-3 (T-lymphoblast acute lymphoblastic leukemia).
Keywords: copper catalysis; coumarins; azacoumarins; indoles; azlactones; microwave heating